Implementasi Kurikulum Pendidikan Antikorupsi di SMA Muhammadiyah 4 Andong Boyolali Tahun Pelajaran 2014/2015 - Hailan, Muhammad, Dr. Abdullah Aly, M.Ag, Dr. Mutohharun Jinan, M.Ag (2016)
Corruption becomes a public attention. On the other hand, the corruption has not solved properly yet and still for from the target, so the corruption should be handled in prevention and education side. Education of anti-corruption must be given start from young and should be included in the teaching learning process,such as elementary school, junior high school and senior high school. In case to create anti-corruption's manner of students. The main material of this education is to implement glorious value about anti-corruption. This plan is postured by SMA Muhammadiyah 4 Andong Boyolali clevery by starting to implement anti-corruption education. The problem statement of this research is how to implement curriculum of anti-corruption education in SMA Muhammadiyah 4 Andong Boyolali, academic year 2014/2015? The aim of this research is to describe the planning, the implementation, and the evaluation of curriculum of anti-corruption education in SMA Muhammadiyah 4 Andong Boyolalali academic year 2014/2015. This is a field research by using phenomenology approach. The data colleting method are interview, observation, and documentation. The data analysis using describtive qualitative. The result of the research and data analysis shows: first, strategy planning; second, program planning, and third, planning of the teaching learning process. The implementation of this curriculum in SMA Muhammadiyah 4 Andong Boyolali user education program based in modul. The evulation model of this curriculum are: first, aspect evaluation of contect emphasized on the goal of curriculum. Second, input evaluation emphasized on the resources (media, material, and modul); third, evaluation aspect of process emphasized on the process of implementation from te begining until ending; fourth, asfect evaluation of product emphasized on the measurement of program result (attitude change, improvement of ability, improvement of attendance).